2014
DOI: 10.1212/wnl.0000000000000568
|View full text |Cite
|
Sign up to set email alerts
|

Early developmental trajectories associated with ASD in infants with tuberous sclerosis complex

Abstract: This prospective study characterizes early developmental markers of ASD in infants with TSC. The early delay in visual reception and fine motor ability in the TSC group as a whole, coupled with the decline in nonverbal ability in infants diagnosed with ASD, suggests a domain-specific pathway to ASD that can inform more targeted interventions for these high-risk infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
94
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 34 publications
6
94
0
5
Order By: Relevance
“…In our prospective study of children with TSC, we found that developmental slowing in nonverbal cognition predicted ASD, highlighting the strong comorbidity of developmental delay and ASD in TSC, 14 and raising the question of whether ASD in TSC actually reflects a more global cognitive impairment rather than specific deficits in social communication.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…In our prospective study of children with TSC, we found that developmental slowing in nonverbal cognition predicted ASD, highlighting the strong comorbidity of developmental delay and ASD in TSC, 14 and raising the question of whether ASD in TSC actually reflects a more global cognitive impairment rather than specific deficits in social communication.…”
Section: Resultsmentioning
confidence: 81%
“…Fifty percent of our TSC cohort met criteria for ASD, consistent with prior studies in TSC. 5,14 Results revealed that children with TSC and ASD demonstrate a profile of social communication impairment that, at the behavioral level, was virtually identical to that of children with nsASD; indeed, there were no individual markers that distinguished the 2 groups. This convergence was observed in the context of high comorbidity between ASD and cognitive impairment in both the TSC/ASD and nsASD groups.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A longitudinal cohort study compared differences between children with ASD with TSC to children with idiopathic ASD and found that syndromic ASD was similar to non-syndromic ASD in terms of their cognitive, behavioral, and social profiles 15 . Evaluation of the AOSI as an objective assessment tool to identify early ASD-associated behaviors in infants with TSC has been shown in a small prospective longitudinal cohort of infants 13 , but using the AOSI to predict later ASD risk in this population has not been previously reported. In 2012, we established the TSC Autism Center of Excellence Research Network (TACERN) , a large multicenter, prospective observational study to identify clinical, structural, and electrophysiological biomarkers predictive of ASD with the overall goal to establish an infrastructure for early detection of ASD and set the stage for future drug trials in patients with TSC who are at high risk for ASD.…”
Section: Introductionmentioning
confidence: 99%